Propriedades psicométricas da versão brasileira do Driving Cognitions Questionnaire - DCQ - Gomes, Isabel Cristina Oliveira (2014)
The present study aimed to evaluate the psychometric properties of the Brazilian version of Driving Cognitions Questionnaire (DCQ) - a scale that assesses cognitions and thoughts related to driving phobia. Furthermore, correlated the results of DCQ with Trait Anxiety Inventory-State (STAI-t and STAI-s) and performed the t-test to check for differences in average of DCQ in the sample groups. The research participants were 200 students from driving schools, of both sexes (65% female), who were preparing for the issuance of driver\'s license in categories A (13.5%) or B (84%). Half of the sample was composed of students who were enrolled in the theoretical stage (classes of legislation) and the other half by students who were attending practical classes (driving lessons). Age varied in the range 18-50 years (M = 39, SD = 7.1 6). As results of the factorial structure DCQ was organized into three factors: factor 1 assesses cognitions related to fear of social criticism in traffic, the factor 2 cognitions related to fear of traffic accidents, the factor 3 cognitions related to fear of suffer panic attack. The scale also showed good internal consistency indices: globally - = 0.90; social subscale - = 0.87; subscale accidents - = 0.77; subscale panic - = 0.73. The correlation between DCQ and STAI-t and STAI-s was significant and had moderate magnitude (r> 0.3, p < 0.01). The result of the t test indicated no significant difference between the total score average of DCQ between men and women, but there were significant differences between the students of practical and theoretical class, and practical class students have a higher number of cognitions on fear of driving (practical class student: t (198) = 2.8, M = 15.04, SD = 11.98; theoretic class student: t (198) = 2.8, M = 10.91 , SD = 8.57, p <0.01). Additional researches with DCQ scale should be conducted in other research contexts and with different samples. Furthermore, it is suggested convergent and discriminant validity of the DCQ with scales that assess anxiety and related disorders. Overall, the findings offered subsidies for the validation of the Brazilian version of the DCQ, suggesting that it carries the promise of being a practical tool to measure the thoughts and cognitions related to fear of driving.